Post-COVID Syndrome: Persistence of Symptoms and Risk Factors (Longitudinal Observational Study) - T. Yu. Agafonova; N. N. Elovikova; O. V. Bronnikova; D. A. Golyadinets (SINAPS LLC, 2024)
The aim - studying the dynamics of symptoms of post-COVID syndrome (depending on the results of depending on the results of the polymerase chain reaction for SARS-CoV-2) and the factors influencing it.Materials and methods. A study is a cohort, observational longitudinal. Stage I: snapshot analysis of medical records of patients with COVID-19 disease history 12 months. (questionnaire for post-COVID syndrome, blood tests). Stage II: questionnaire repeat, disease history - 24 months. There were test (positive polymerase chain reaction, 138 people) and control (negative polymerase chain reaction, 87 people) groups. Statistical analysis: package Statistica 13.5.0.17.Results. 1 year after COVID-19, the frequency of manifestations of post-COVID syndrome was (test vs control group): asthenia 63 % vs 64 %, decreased quality of life 59 % vs 56 %, respiratory syndrome 60 % vs 49 %, arthralgia 55 % vs 49 %, cardiac syndrome 47 % vs 46 % (the difference is not significant); symptoms are associated with female gender (r=0.231- 0.379), severity of COVID-19 (r=0.187-0.425), D-dimer (r=0.244-0.328). After 2 years, the frequency of symptoms was: asthenia 43 % vs 45 %, cardiac symptoms 23 % vs 15 %, respiratory symptoms 18 % vs 22 %, skin manifestations 8 % vs 12 %, decreased quality of life 7 % vs 9 %, the difference is not significant; symptoms are associated with age (r=0.208-0.402). During two years, symptoms have been correlating with platelets (r=-0.322-0.403), liver enzymes (r=0.216-0.298), blood lipids (r=0.188-0.257).Conclusions. The severity of post-COVID syndrome does not depend on the results of the polymerase chain reaction for SARS-CoV-2. The frequency of cardiac and respiratory syndromes after 2 years decreases by 2-3 times; quality of life improves. Asthenia is the most long-term syndrome. Risk factors for post-COVID syndrome during the 1st year - severity of COVID-19, female gender, D-dimer level; from the 2nd year - age. For two years after COVID-19, monitoring of liver enzymes, lipids, and platelets is required.